Fracture toughness of glasses and hydroxyapatite: A comparative study of 7 methods by using Vickers indenter. Issue 11 (15th August 2016) - Hervas, I.; Montagne, A.; Van Gorp, A.; Bentoumi, M.; Thuault, A.; Iost, A.
Abstract: Numerous methods have been proposed to estimate the indentation fracture toughness Kic for brittle materials. These methods generally uses formulæ established from empirical correlations between critical applied force, or average crack length, and classical fracture mechanics tests. This study compares several models of fracture toughness calculation obtained by using Vickers indenters. Two optical glasses (Crown and Flint), one vitroceramic (Zerodur) and one ceramic (hydroxyapatite) are tested. Fracture toughness and hardness are obtained by using instrumented Vickers indentation at micrometer scale. Young's moduli are obtained by instrumented Berkovich indentation at nanometer scale. Fracture toughness is calculated with models involving crack length measurements, and by models free of crack length measurements by considering critical force, chipping, pop-in. Finally, method based on the cracking energy, commonly employed for coated materials is also used. The aim of this work is to compare seven methods, which enable the facture toughness determination, on four brittle materials. To do so, it was necessary to determine some specific constant in the case of Vickers tip use. On the one hand, results show that methods using crack length, critical force, edge chipping or pop-in lead to comparable results, and the advantages and drawbacks are highlighted. On the other hand, the indentation energy method leads to underestimated results of about 20%.